Analysis of Legends in Translations - Zulfiya Olimjonovna Mirabdullayeva; Egasheva Marjona (Journal of Higher Education and Academic Advancement, 2024)
In this article, one of the oldest genres of Uzbek folk art in translations, it narrates events and incidents related to social life on the basis of fictional fiction. Because it was created in the process of people's desire to know and understand natural phenomena and social events. That is why the legend provides concise information about social life, people's outlook, customs and historical events.